(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2026)
Disaster means a catastrophe, mishap, calamity or grave occurrence in any area arising from natural or manmade causes or by accident or negligence which results in substantial loss of life or human suffering or damage to, and destruction of property, or damage to, or degradation of, environment and is of such nature or magnitude as to be beyond the copping capacity of the community of the affected area. The impact of natural disasters in Himachal Pradesh has been witnessing damages almost during every rainy, winter and summer season also due to excessive rain, avalanches, cloudbursts, landslides, flash floods hailstorms and droughts where as earthquake disaster took place occasionally. Extensive damages are caused to the infrastructure like roads, bridges, drinking water supply schemes, irrigation projects/ schemes, hydroelectric projects, destruction of forest wealth, besides taking its toll of human and cattle lives and destruction of private properties. Over the last decade of 20th century and recent past Himachal Pradesh is facing nature wrath in diverse forms one calamity has followed in the wake of the other. During the period from 1990 to 2005 a search of loss due to natural disasters through govt. record reveals that during this period the total loss to the public property in the state is estimated to be Rr.163530.82 lacs, housing sector and cowsheds etc. to the extent of Rs. 92340.46 lacs and 274.778 lacs population affected. Due to natural disasters 828 human lives and 18033 heads of cattle have been lost. An extensive loss to the agriculture and horticulture sectors has also been recorded in the state.